2013
DOI: 10.4254/wjh.v5.i7.364
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of traditional chemoembolization with or without sorafenib for hepatocellular carcinoma

Abstract: AIM:To compare the overall survival (OS) and progression-free survival (PFS) with associated adverse events (AE) in patients with unresectable hepatocellular carcinoma (HCC) treated with transarterial chemoembolization (TACE) + sorafenib vs TACE alone. METHODS:In this retrospective cohort study we collected data on all consecutive patients with a diagnosis of unresectable HCC between 2007 and 2011 who had been treated with TACE + sorafenib or TACE alone. We hypothesized that the combination therapy is superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…This contradicts studies showing the effectiveness of TACE with sorafenib for intermediate-advanced HCC [ 11 14 ], but might be explained by the inclusion of more advanced stage patients with fewer CRs in those studies. On the other hand, we confirm the results of another report [ 18 ] showing that TACE plus sorafenib achieved a comparable effectiveness to treatment with TACE alone for patients with HCC (most patients were BCLC stage A and B). Similarly, Cabrera et al [ 12 ] reported that the combination of TACE and sorafenib achieved a median survival time of 18.5 months for patients with BCLC stage B.…”
Section: Discussionsupporting
confidence: 90%
“…This contradicts studies showing the effectiveness of TACE with sorafenib for intermediate-advanced HCC [ 11 14 ], but might be explained by the inclusion of more advanced stage patients with fewer CRs in those studies. On the other hand, we confirm the results of another report [ 18 ] showing that TACE plus sorafenib achieved a comparable effectiveness to treatment with TACE alone for patients with HCC (most patients were BCLC stage A and B). Similarly, Cabrera et al [ 12 ] reported that the combination of TACE and sorafenib achieved a median survival time of 18.5 months for patients with BCLC stage B.…”
Section: Discussionsupporting
confidence: 90%
“…18 TACE can cause local hypoxia, which increases levels of vascular endothelial growth factor receptor (VEGF). 18 TACE can cause local hypoxia, which increases levels of vascular endothelial growth factor receptor (VEGF).…”
Section: Sorafenibmentioning
confidence: 99%
“…18 Researchers suggested that the combination therapy of TACE plus sorafenib was safe and equally effective to TACE alone in patients with unresectable hepatocellular carcinoma. The most common adverse reactions reported for both treatment groups were abdominal pain, nausea, vomiting, and mild elevation of liver enzymes.…”
Section: Sorafenibmentioning
confidence: 99%
“…Molecular biology studies have shown that the level of vascular endothelial growth factor (VEGF) usually increases locally and systemically after TACE treatment is performed, whereas sorafenib can inhibit the activity of VEGF receptors [11]. Thus, in recent years a large amount of studies have tried to combine sorafenib with TACE for patients with unresectable HCC, while the results were controversial [12]. Combination therapy may bring benefits for unresectable HCC patients in terms of TTP but not OS.…”
Section: Transarterial Chemoembolization With Doxorubicin-eluting Micmentioning
confidence: 99%